Formation of the system of control indicators of external fundraising for engineering enterprises - Партин, Галина Остапівна; Задерецька, Роксолана Іванівна; Горбай, Богдан Олегович (Technology audit and production reserves, 2015)
The method of forming the system of process indicators for external fundraising is considered in the article. The main aim of the study is to determine the key aspects of the control system and the development of sets of indicators on which it is advisable to monitor the processes of external fundraising. Therefore, it was revealed that system of indicators for monitoring external fundraising should help the enterprise adapt to the external business environment and facilitate the financing regulation processes of industrial and economic activity. The key task of control is matching external fundraising processes to established strategic, tactical and operational objectives of the company. It was developed the complex system of external fundraising indicators, which consists of four groups of indicators: activity, structure, risk and overall effectiveness that allows monitoring adverse changes in key parameters of external fundraising and effectively adjust the process of implementation of management decisions on external fundraising for engineering enterprises. Research results can be applied by financial managers to access the administrative decisions in the process of fundraising from the external sources.